(untitled) (Research, Society and Development, 2019)
Is recurrent in official speeches, academics and also in school space on the role of experimental classes as motivating for learning students. That role is often as essential to the improvement, change and transformation of teaching science. In view of this object and your complexity, the present research is of relevance to fetch interpret the opinions of students of 2nd year of high school training about classes experimental chemistry. The approach chosen to satisfy this goal was a qualitative research, using interviews with four open questions for data collection, those that were interpreted in the light of the assumptions bakhtinianos of enunciation and the discussion about the use of experimentation in teaching. The results showed the lack of contact of students with experiments, demonstrating the existence of a dichotomy between theory and practice and, therefore, that the acting teacher is out of context. What sparked a vision confused about the Chemistry discipline; on the other hand, some students recognize your importance, and on the other, the difficulty on your assimilation. These developments expose the plot of a phenomenon rife with senses and meanings that deserve to be discussed.